Mortalidade perinatal e as suas relações com os processos socioespaciais - Barros, Amanda Peres Zubiaurre de (2021)
The Perinatal Mortality Rate is considered an expressive indicator of the conditions of prenatal care, childbirth, and the newborn, in addition to access to health services. The objective was to analyze the relationship between socio-spatial processes and perinatal mortality. This is an epidemiological study, of an ecological and retrospective type, which included the deaths of the 4th regional health coordinator of the southern state of Brazil, with data collection from medical records. The sample consisted of early fetal and neonatal deaths, by occurrence in the municipality of Santa Maria, from 2011 to 2018. Data were analyzed in a descriptive, inferential, and spatial manner. It was appreciated by the Ethics and Research Committee of the Federal University of Santa Maria, with opinion approved under number 4,206,244. The results showed that most women did not receive prenatal care properly; stillborn or newborns were male, with very or extremely low birth weight and presented extreme prematurity. Regarding neonatal deaths, most occurred on the first day of life. The main manner of delivery was vaginal. Most live births had Apgar in the 1st minute suggestive of precarious conditions at birth or severe asphyxia. Premature labor was the most prevalent complication. In the bivariate analysis, there was a statistically significant relationship between the variable’s previous pregnancy losses and use of drugs. In the spatial analysis, 261 deaths were georeferenced. Regionally, the areas with the highest perinatal mortality rates were pointed out in the municipalities of Toropi, São João do Polêsine, Mata, Silveira Martins and Faxinal do Soturno. In the cartographic representation of clusters, there was the presence of neighboring areas with clusters of deaths. In Santa Maria-RS, the Kernel map showed high density areas in the west and Midwest regions. The concentration of deaths presents a path that follows areas of irregular occupation and the railway line, which are regions of intense vulnerability and poverty in the city, but geographically close to health services. Furthermore, deaths happened in areas of high or very high social deprivation.